LASER AND INCISIONAL MYRINGOTOMY IN OTITIS MEDIA WITH EFFUSION-A COMPARATIVE STUDY - Yousaf, Mohammad; Malik, Sohail Ahmad; Zada, Bakht (Journal of Ayub Medical College Abbottabad, 2014)
Background: Otitis media with effusion (OME) or middle ear effusion (MEE) is a common cause of hearing difficulty in children. MEE must be detected early and managed properly to prevent conductive hearing loss in children. It was aimed to compare results of laser myringotomy and conventional myringotomy in terms of hearing improvement, recurrence of MEE and time to put ventilation tube. Methods: This randomized control trial was conducted from February 2012 to April 2014. Children of 4 years age or older with MEE were included in the study. These children were investigated with Pure tone audiometry (PTA) and tympanometry to confirm conductive hearing loss. X-Ray nasopharynx lateral view was performed for adenoids. Sixty-six patients were randomly assigned in to 2 groups, (1) treated with laser myringotomy and (2) treated with classical myringotomy. The ears were evaluated for MEE, for presence of perforation and level of hearing. Results: A total of 98 ears in 66 patients underwent intervention. Middle ear effusion cleared in 44 out of 48 ears with laser myringotomy (LM) as compared to34 out of 50 ears with incisional myringotomy. The perforation was still patent in 36 ears treated with LM while it was found closed in all 50 ears with conventional myringotomy after 2 weeks. The hearing level improved with LM by 10-15 dB after first 3 months. Conclusion: The aim of management in otitis media with effusion is ventilation of tympanic cavity. Laser myringotomy is a best alternative to conventional one. It also has comparable results with ventilation tubes (VT). The ears with refractory or recurrent MEE should have VT insertion. Keywords: otitis media with effusion, middle ear effusion, laser myringotomy, adenoids, ventilation tubes, tympanometry